An efficient method of analysis of heat transfer during plane strain upsetting of a viscoplastic strip. Issue 5 (27th February 2019) - Alexandrov, Sergei; Miszuris, Wiktoria; Lang, Lihui
Abstract: A solution for the transient heat transfer during plane strain upsetting of a viscoplastic strip has been developed using a Lagrangian coordinate system and the Green's function available in the literature. A general approximate solution for stress and velocity found elsewhere has been used. In contrast to conventional viscoplastic models adopted in theoretical analyses of metal forming processes, the model considered in the present paper includes a saturation stress. This model used in the conjunction with the maximum friction law predicts the localization of plastic deformation in the vicinity of the friction surface. In turn, localized plastic deformation and temperature are responsible for the generation of a very narrow layer with drastically modified microstructure near the friction surface. The appearance of such layers is reported in numerous experimental works. Abstract : A solution for the transient heat transfer during plane strain upsetting of a viscoplastic strip has been developed using a Lagrangian coordinate system and the Green's function available in the literature. A general approximate solution for stress and velocity found elsewhere has been used. In contrast to conventional viscoplastic models adopted in theoretical analyses of metal forming processes, the model considered in the present paper includes a saturation stress. This model used in the conjunction with the maximum friction law predicts the localization of plastic deformation in the vicinity of the friction surface. In turn, localized plastic deformation and temperature are responsible for the generation of a very narrow layer with drastically modified microstructure near the friction surface. The appearance of such layers is reported in numerous experimental works.